Psychological Need-Based Experiences as Energizing Processes for Mothers' Identity Formation. - Arden, Adi; Katz, Idit; Slobodin, Ortal (Journal of Child & Family Studies, 2023)
Research anchored in self-determination theory (SDT) has demonstrated the positive effects of parental need support on children's ability to formulate a clear and integrated identity. However, much less is known about what motivates parents' identity formation processes and how these processes are related to their parenting practices. Integrating SDT with identity formation theorizing, this study investigated mothers' identity processing style as a possible mediator of the relationship between their own need-based experiences and their parenting practice. In total, 429 Israeli mothers of preschool children (age 3–6 years) participated in the study. Participants provided information about their experience of psychological need satisfaction and frustration, identity processing styles, identity commitment, and parenting practices. Results showed that mothers whose basic psychological needs were satisfied were more likely to provide autonomy support and structure in their interactions with their children. This relationship was mediated by mothers' tendency to adopt a more informational identity processing style and higher identity commitment. In contrast, mothers' experiences of need frustration were associated with psychologically controlling and chaotic practices through diffuse-avoidant identity processing style. A normative identity style mediated the association between mothers' need frustration and their use of psychological control and structure. Our findings suggest that the satisfaction of mothers' basic needs provides them the inner resources to explore existing identity options and facilitates greater self-organization and integrated identity development. In contrast, the frustration of mothers' psychological needs has an energy-depleting effect on mothers. Highlights: This study integrates identity formation theorizing with self-determination theory. Mothers' need satisfaction is an essential resource for their parenting. Mothers' informational identity style was related to autonomy-supportive and structuring parenting. Mothers' diffuse avoidant identity style was related to psychologically controlling, chaotic parenting. Mothers' normative identity style was related to psychologically controlling and structuring parenting.